What medications are safe and effective in pediatric patients with depression?. Issue 9 (September 2016) - Haynes, James; Shepherd, Michael
Abstract : Evidence‐Based Answer : Escitalopram is likely the most consistently efficacious medication in treating multiple aspects of pediatric depression (SOR: A, meta‐analyses of RCTs). Paroxetine and citalopram appear to be ineffective in treating pediatric depression. All medications slightly increase the risk of suicidal ideation and behavior, with sertraline having the highest risk and mirtazapine and escitalopram having the lowest risk (SOR: B, metaanalyses of RCTs with heterogeneity).